Biochar derived from pig manure with ability to reduce the availability of Pb in contaminated agricultural soils - Cabello-Torres, Rita Jaqueline (2021)
The use of organic amendments improves the quality and increases the fertility of the soils due to their adsorption properties, stimulates nutrient cycling and can be used to reduce the availability of heavy metals. The main objective of the research was to evaluate the effect of biochar (BC) derived from pig manure on the availability of Pb in a contaminated and limed agricultural soil. A randomized experimental design was applied, the pig manure was dried at room temperature (23 °C) and pyrolyzed at 500 °C for 2 h. Doses of 5%, 10% and 20% of BC were applied to the Pb soils contaminated (165.7 mg/kg), that were arranged in 2 kg pots except for the control sample, and Lactuca sativa was subsequently grown cultivated to evaluate the Pb availability. The results indicated an improvement in soil quality at higher BC dose, increase of 0.34 pH units, decrease of Pb extracted by EDTA (27% to 62% of decrease), and non-significant Pb content in leachates (< 1 mg Pb/L) and no detection in plant roots (< 0.01 mg/kg), except for the control plant (0.7 mg Pb/kg) in the original soil. A logarithmic relational model between BC dose and Pb adsorbed in the soil was obtained (R2 = 0.9938, p < 0.05) showing that the decrease of Pb availability in the soil increased for higher BC doses, which represents an eco-friendly remediation alternative. It is recommended to investigate the interaction relationships between the soil quality parameters and to establish functional models of bioaccumulation and extractable metal of the amended soil.